Assessment of educational performance of nurses in neonatal intensive care unit from parents' perspective - Morteza Mansourian; Arash Ziapour; Mohammad Kazemian; Zhilla Heydarpoor Damanabad; Babk Rastegarimehr; Amin Mirzaei; Omid Safari; Reza Pourmirza Kalhori; Mohammadreza Mansouri Arani (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: One of the key elements in family-centered care is educating parents with hospitalized infant at intensive care unit. Education is a fundamental role of nursing at intensive care units to satisfy parents and accelerate disease progression that eventually reduces hospital re-admission. MATERIALS AND METHODS: This was a cross-sectional study conducted in 2018, and the study population was admitted infants (n = 90) in the neonatal intensive care unit (NICU) of Shahid Beheshti University of Medical Sciences hospitals. We used a questionnaire including sociodemographic characteristics and performance of nurses in educating parents. Nurses' performance was assessed in five major areas composed of family-centered care, delivering cares according to individualized needs, education on equipment, basic needs of infants, and finally, nutritional education. All statistical analyses were conducted using SPSS version 22. The data were analyzed using t-test, ANOVA, and nonparametric tests. RESULTS: Findings from the current study indicated that nurses performed their educational role weakly (37% of standard level). We also found that nurses who participated in neonatal educational courses had better performance compared to their counterparts. The results showed that year of experiences working as a clinical nurse was significantly associated (P < 0.05) with performing standard education. CONCLUSION: Our findings indicated that nurses performed their educational role weakly which might be due to staff shortage, heavy workload, and lack of time for educating parents. Therefore, it is necessary to improve the quality of education among nurses working at the NICUs and provide the necessary standards and indicators to evaluate this important task.